Do we worship the same God? : Jews, Christians, and Muslims in dialogue - Volf, Miroslav (William B. Eerdmans Pub. Co., 2012)
Often the differences between the three Abrahamic religions -- Judaism, Christianity, and Islam -- seem more obvious than their commonalities, leading to the question "Do we worship the same God?" Can the answer be "yes" without denying our differences? This volume brings Jewish, Christian, and Muslim philosophers and theologians together to answer this question, offering rare insight into how representatives of each religion view the other monotheistic faiths. Each of their contributions uniquely approaches the primary question from a philosophical perspective that is informed by the practice of worship and prayer. Concepts covered include "sameness" and "oneness," the nature of God, epistemology, and the Trinity. Do We Worship the Same God? models serious-minded, honest, and respectful interreligious dialogue and gives us new ways to address an ongoing question